Optimizing Bugnay mead wine – Wild berries (Antidesma bunius ) for consumer preference - Evelyn, B Cristobal (Plant Science Today, 2025)
The primary objectives of this study were to develop a mead wine with bugnay fruit flavor, determine its alcohol content, and compare the sensory acceptability of two samples. A sensory evaluation was conducted to characterize the wines based on appearance, aroma, taste and texture. To measure consumer acceptance, a Likert scale was employed, with the highest score representing strong preference and the lowest indicating strong dislike. The t-test was used to analyze differences in acceptability between the two samples. The results indicated that the provided sample exhibited an alcohol content of 19.21%. Additionally, a sensory analysis revealed that sample 2 was significantly preferred across all evaluated quality attributes. Consequently, sample 2 demonstrated higher acceptability compared to sample 1. These findings suggest that mead wine with bugnay fruit flavor is highly acceptable and has potential as a small-scale income-generating enterprise for rural communities.